2012
DOI: 10.1111/j.1530-9290.2012.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Part Manufacturing and Vehicle Assembly Component of the Vehicle Life Cycle Inventory

Abstract: Keywords:automobile industrial ecology life cycle energy analysis life cycle inventory (LCI) material/transformation process distribution vehicle and parts manufacturing Supporting information is available on the JIE Web site SummaryA model is presented for calculating the environmental burdens of the part manufacturing and vehicle assembly (VMA) stage of the vehicle life cycle. The model is based on a process-level approach, accounting for all significant materials by their transformation processes (aluminum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 7 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…We modelled device assembly assuming an electricity input of approximately 1.5 kWh/kg with an assumed electrical energy/ heat ratio of 2:1 (Sullivan et al 2013) 1 for the assembly of structural components, PTO components, mooring and foundations and the electrical connection.…”
Section: Assembly and Manufacturingmentioning
confidence: 99%
“…We modelled device assembly assuming an electricity input of approximately 1.5 kWh/kg with an assumed electrical energy/ heat ratio of 2:1 (Sullivan et al 2013) 1 for the assembly of structural components, PTO components, mooring and foundations and the electrical connection.…”
Section: Assembly and Manufacturingmentioning
confidence: 99%
“…Hence, the only factor which contributes to energy variance in this period is the change in vehicle fuel economy which ranged between 9.23 to 10.55 km/L. Additionally, Sullivan et al (2012) found that the vehicle assembly phase of the vehicle life cycle inventory shows a coefficient of variance of 8.4% for energy intensity. Lastly, the end-of-life portion of the vehicle's life cycle usually has the least total energy consumption.…”
Section: Monte Carlo Simulations and Analysis Of Variance (Temporality)mentioning
confidence: 95%
“…Most existing studies on the transport energy consumption in cities have focused on the tank to wheel (TTW) energy consumption during the operational phase. Meanwhile, the significant impact of energy consumption during the manufacturing phase, especially material structure, has been widely highlighted [28,[42][43][44]. As such, this study considers energy consumption during the phases of material structure and operation among all lifecycle stages.…”
Section: Boundary Of Energy Consumptionmentioning
confidence: 99%